Geology and demarcation of the groundwater potential zones using Electrical Resistivity Imaging (Eri) in Kuala Balah - Enalina Suhaimi (2019)
A study entitled Geology and Demarcation of the groundwater potential zones using Electrical Resistivity Imaging (ERI) in Kuala Balah has been conducted. The research area is located in Kuala Balah which is part of sub district of Jeli Kelantan, Malaysia. Presently the area is totally depending on surface water which cannot be promise regular supply during drought time and also easy to contaminate by the surface activities. Keeping in this view, the present research provides an update geological map on a scale of 1: 25,000 and demarcate groundwater potential zone in Kuala Balah, Kelantan. The methodology of this research involve preliminary studies, field studies, laboratory work, data processing, and data interpretation. For first location, the Pole dipole electrode arrangement is used while second and third location, the Schlumberger is used. Each survey line spread 200 meters with 5 meters spacing. The resistivity and induced polarization data were collected by using ABEM Terrameter LS. After data acquisition, the procedure continues to the data processing and inversion using RES2DINV software. The processed data interpreted by overlapping the resistivity value and the IP value on 2 D profile which shows the occurrence of the bedrock, coarse grain sand, clay lenses, and geological structure like fault and fracture. Further this results show that groundwater potential zone in the form confined aquifer and fractured zone. Geological mapping and geophysical survey has been proved as an effective way to find the groundwater potential zones. This research project represents a major step toward new development of water supply.